Methodological aspects of values for determining the physical load in sport. - Chernozub A.A (Kharkov National Pedagogical University, 2012)
The main aspects of the control system of training in sport and identified two methodological concepts determine the amount of physical activity during the training sessions. It is established that the physical training and sports activities in the course of employment estimate the value of physical activity mainly due to the reaction rates of the functional systems of the body to an external stimulus. Such an assessment, especially in a narrow range of controllable parameters (for the reaction of the cardiovascular and respiratory systems), is more theoretical in nature and does not allow to clearly define the critical load levels for a particular organism. This problem highlights the need to use a single, integrated, suitable for precise mathematical analysis of the universal, possibly conditional, indicator or criteria for evaluating physical activity. Development of this criterion will optimize the training process at different stages of training opportunities tailored to individual athletes.